Penyuluhan Komunikasi Kesehatan Efektif Bagi Para Kader Posyandu di Kelurahan Maleer, Kecamatan Batununggal, Kota Bandung - Fitriyani, Sani; Nurrachman, Iman (LPPM Politeknik Piksi Ganesha, 2024)
Posyandu cadres play a crucial role in supporting community health services at the village level, particularly in delivering health information to mothers and children. However, the effectiveness of health communication often becomes a challenge that can affect community understanding and participation. This community service activity aims to enhance the health communication skills of posyandu cadres in Maleer Village, Batununggal Subdistrict, Bandung City. The methods used include counseling, interactive discussions, and effective communication simulations. The materials presented cover interpersonal communication techniques, delivering information based on community needs, and utilizing simple communication media. The results of this activity indicate an improvement in cadres' understanding and skills in effectively conveying health information, which is expected to raise awareness and improve community health behaviors. This program also strengthens the capacity of cadres as the frontline of health services while supporting efforts to enhance the quality of posyandu services in the area. Out of 131 participants, 21 individuals (15.9%) demonstrated a strong understanding, 27 individuals (20.5%) showed a moderate understanding, and 84 individuals (63.6%) had a good grasp of the material on effective health communication counseling.